Priming Factors Related to Burn Injury among People in Bangladesh - Khan, Abid Hasan; Bhuiyan, Saruar Hossain; Hossain, Zahid (Journal of Health and Allied Sciences NU, 2023)
Background Burns cause the most severe injuries and are a major public health concern worldwide. It is common in third-world countries and it greatly increases mortality and illness there. Because of the long period of time spent in the hospital and the effort required to recover from a burn, it is one of the most costly injuries to treat.Objectives The aim of this study was to identify the priming factors related to burn injury among people in Bangladesh.Materials and Methods The study design was cross-sectional. Total 121 samples were selected conveniently for the study and the study was conducted in several hospital settings in Chittagong, Savar and Dhaka city like Chittagong Medical College Hospital, Enam Medical College Hospital, and Sheikh Hasina Burn Hospital. Data was collected by using a self-administered questionnaire.Statistical Analysis Descriptive and inferential statistics (chi-squared test) were used for data analysis that focused through tables.Results On average, people were 22.43 (14.399) years old. Of the total of 121 patients, 48.1% were female (n = 58) and 52.1% were male (n = 63). Among the participants, 56.2% (n = 68) were hurt accidentally, 33.9% (n = 41) were injured on the job, 2.5% (n = 3) were harmed intentionally, and 7.4% (n = 9) were injured while preparing food. In case of occurrence, 37.2% (n = 45) were burned by fire, 38.8% (n = 47) were electrical burn and 23.9% (n = 29) were chemical or scald type burn.Conclusions Most burn injuries are accidental, such as cooking fires, hot water, electric lines, and acid throwing that are significantly considered as the priming factors of burn injury among people in Bangladesh. The lack of awareness and ignorance causes these accidents and insufficient training causes most the electrical burns.
Keywords: priming factors; burn injury; types of burn injury